Activation of the anticancer drugs cyclophosphamide and ifosfamide by cytochrome P450 BM3 mutants. Issue 1 (5th January 2015) - Vredenburg, Galvin; den Braver-Sewradj, Shalenie; van Vugt-Lussenburg, Barbara M.A.; Vermeulen, Nico P.E.; Commandeur, Jan N.M.; Vos, J. Chris
Highlights We identified CYP BM3 mutants showing very efficient activation of CPA and IFA. CYP BM3 mutants showed very low formation of neuro- and nephrotoxic byproducts. Cytotoxicity of CPA and IFA metabolism was confirmed in human U2OS cells. CYP BM3 was used as a novel extracellular bioactivation tool in cellular assays.